IMAGINATIVE AND ARTISTIC-AESTHETIC PROPERTIES OF KARAKALPAK LIPS (TAMADDUN NURI JURNALI, 2025)
The article typologically analyzes artistic features of proverbs and sayings of Karakalpak folklore. The closeness, similarity and unique characteristics of such words were scientifically analyzed.